Akata woman - Okorafor, Nnedi (Okorafor, Nnedi. Nsibidi scripts series ;, 2022)
With the help of her friends, fifteen-year-old Sunny embarks on a mission to find a precious object and return it to the spider deity Udide, but defeating the guardians of Udide's ghazal will put all of Sunny's hard lessons and abilities to the test.